Desain Media Pembelajaran Interaktif "Sumber Daya Alam" dengan Kombinasi Vidio Edukasi (Brain POP) dan Kuis (Kahoot!) untuk Kelas 4 SD (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
Technology-based learning media have now become a primary choice in supporting the learning process in elementary schools, in line with the development of the digital era and the growing demand for more innovative learning approaches. The utilization of technology in education is expected to enhance the quality of teaching and learning processes and encourage active student engagement. One technology-based learning medium considered effective and engaging is BrainPOP, a digital learning platform that presents educational content through interactive animated videos, quizzes, simulations, and various supporting activities designed to suit the characteristics of elementary school students. The selection of BrainPOP is based on its advantages in increasing students’ learning interest, facilitating the understanding of abstract concepts by making them more concrete, and enhancing students’ motivation and retention of learning materials. The visual, communicative, and interactive presentation of content enables students to learn in a more enjoyable and less monotonous manner. This medium is capable of creating an engaging, effective, and student-centered learning atmosphere, thereby fostering an active, creative, and enjoyable learning environment. Therefore, the use of BrainPOP in the learning process is expected not only to improve students’ learning outcomes but also to optimally and sustainably develop their interest, motivation, and engagement in learning.